2022
DOI: 10.1136/heartjnl-2022-320934
|View full text |Cite
|
Sign up to set email alerts
|

Mortality after multivessel revascularisation involving the proximal left anterior descending artery

Abstract: ObjectiveWe sought to investigate whether long-term clinical outcomes differ following percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) in patients with three-vessel disease (3VD) and lesions in the proximal left anterior descending artery (P-LAD).MethodsThis post-hoc analysis of the Synergy between PCI with Taxus and Cardiac Surgery (SYNTAX) Extended Survival study included patients with 3VD who were classified according to the presence or absence of lesions located in the P-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“… 8 The SYNTAX (Synergy between PCI with Taxus and Cardiac Surgery) score was also significantly higher in the proximal LAD group than in the nonproximal LAD group. 7 These results indicated that ischemia caused by proximal LAD lesions put more myocardium at risk and lead to a worse prognosis. However, the SORT‐OUT II study found opposite results.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“… 8 The SYNTAX (Synergy between PCI with Taxus and Cardiac Surgery) score was also significantly higher in the proximal LAD group than in the nonproximal LAD group. 7 These results indicated that ischemia caused by proximal LAD lesions put more myocardium at risk and lead to a worse prognosis. However, the SORT‐OUT II study found opposite results.…”
Section: Discussionmentioning
confidence: 91%
“…The TWENTE I‐III study also found that the rate of the device‐oriented composite clinical endpoint (cardiac death, target vessel myocardial infarction, or target lesion revascularization) was higher in proximal LAD lesions 8 . The SYNTAX (Synergy between PCI with Taxus and Cardiac Surgery) score was also significantly higher in the proximal LAD group than in the nonproximal LAD group 7 . These results indicated that ischemia caused by proximal LAD lesions put more myocardium at risk and lead to a worse prognosis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations